Stable cesium (133Cs) uptake by Calla palustris from different substrates - Rinaldi, Federica; Komínková, Dana; Berchová, Kateřina; Daguenet, Jeremy; Pecharová, Emilie (Ecotoxicology and environmental safety, 2017)
The uptake of stable cesium (133Cs) by Calla palustris was evaluated from four different substrates: water, soil, keramzit (a clay granule) and water with the addition of a potassium compound, after an eight days exposure to a solution of 0.5mM cesium chloride. Stable cesium was used because it is commonly supposed that its uptake by plants is the same of that of radiocesium (137Cs). The plants were differentiated in their parts (roots, healthy leaves, dead leaves and flowers) and analyzed with ICP-MS. The lowest average concentration of absorbed Cs was found in plants exposed in soil (0.7mg/kg, S.D.=96.8), while the highest in plants exposed in water (147mg/kg, S.D.=51.7). During the experiment the water planted plants removed 31.6% of provided Cs while those planted in soil removed only 0.06%. The addition of potassium to water was tested because of the competition effect that arises between these two elements: this effect was confirmed with the result that the average uptake in the presence of potassium was lower (41mg/kg in exposed plants, S.D.=76.1). The uptake was also lower in the solid-based substrates (soil and keramzit), because of the known tendency of Cs to bind with soil particles, thus becoming less available to plants. There was no evidence that the different parts of the plant showed different uptake effectiveness, or that the health of the plant (evaluated with a qualitative method) had any effect on the uptake of Cs.
Keywords: Calla (rostlina); půda; voda; Minerals; Soil; minerály; Stable cesium; Environmental Pollutants; draslík; cesium; Potassium; kořeny rostlin; Plant Components, Aerial; Radiocesium; nadzemní části rostlin; Cesium; Calla Plant; Chlorides; (133)Cs; Phytoremediation; chloridy; Biodegradation, Environmental; biodegradace; Uptake; Plant Roots; Water; látky znečišťující životní prostředí; Calla palustris